The planning system and housing supply - Meehan, Brian (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2003)
Section 1.0 of this paper outlines the evolution of housing supply in the context of planning and housing legislation/policy. In this context, Section 2.0 evaluates Part V of the Planning and Development Act 2000, as amended in 2002, which relates to housing supply and its provisions for private, social and affordable housing.
Papers from practice
Keywords: Urban geography -- Ireland